2014
DOI: 10.1021/bi5006317
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Substrate Selectivity of Ubiquitin C-Terminal Hydrolase-L3 Using Engineered α-Linked Ubiquitin Substrates

Abstract: The ubiquitin-proteasome system (UPS) is highly complex and entails the concerted actions of many enzymes that function to ubiquitinate proteins targeted to the proteasome as well as enzymes that remove and recycle ubiquitin for additional rounds of proteolysis. Ubiquitin C-terminal hydrolase-L3 (UCH-L3) is a human cytosolic deubiquitinase whose precise biological function is not known. It is believed to hydrolyze small peptides or chemical adducts from the C-terminus of ubiquitin that may be remnant from prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Reduced thermal stability was also reported experimentally due to ubiquitination of the β1 domain of streptococcal protein G (Gβ1) and the B domain of staphylococcal protein A (SpAB). Several variants of the Gβ1 and SpA B proteins were linked to a monomeric ubiquitin at the N-terminus . Most of the variants showed lower melting temperatures with an average difference between the free Gb1 (SpA B ) variant and the Gb1 (SpA B ) variant fused to Ub of 7.2 ± 3.7 °C (1.8 ± 1.5 °C).…”
Section: Biological Implications Of Destabilization Following Protein...mentioning
confidence: 99%
“…Reduced thermal stability was also reported experimentally due to ubiquitination of the β1 domain of streptococcal protein G (Gβ1) and the B domain of staphylococcal protein A (SpAB). Several variants of the Gβ1 and SpA B proteins were linked to a monomeric ubiquitin at the N-terminus . Most of the variants showed lower melting temperatures with an average difference between the free Gb1 (SpA B ) variant and the Gb1 (SpA B ) variant fused to Ub of 7.2 ± 3.7 °C (1.8 ± 1.5 °C).…”
Section: Biological Implications Of Destabilization Following Protein...mentioning
confidence: 99%
“…The dramatic destabilization observed in ubiquitination of Ubc7 at specific sites was mostly attributed to changes in the unfolded state. Furthermore, it was recently shown that in vitro attachment of Ub reduces the thermodynamic stability of the modified protein (Ub C‐terminal hydrolase‐L3) …”
Section: Introductionmentioning
confidence: 99%
“…It was computationally shown that protein tethering may result in intrinsic destabilization . Experimentally, both destabilization and stabilization were observed upon tethering or cross‐linking . These effects may have different origins related to changes in the dynamics and energetics of either the folded or unfolded state.…”
Section: Introductionmentioning
confidence: 99%
“…Early study showed that UCH-L3 mRNA level was significantly up-regulated in breast cancer tissue compared to adjacent normal breast tissue and had significantly a positive correlation with histological grades and negative correlation with estrogen and progesterone receptor status, also suggesting the possible involvement of UCH-L3 in the pathogenesis and progression of breast cancer [19]. UCH-L3 hydrolysis is significantly influenced by thermal stability [24]. A recent study showed that UCH-L3 might play a role in the regulation of autophagic death of leukemia [25].…”
Section: Discussionmentioning
confidence: 99%